The Effect of The Learning Cycle 5e Model On Mastery of Concepts and Creative Thinking Students On Renewable Energy Materials At SMAN 1 Gerung - Barinta Nur Respasari; Joni Rokhmat; I Wayan Gunada; Hikmawati; Stefanie Astrid Aipassa (Postgraduate Program, University of Mataram, 2024)
This study aims to identify the effect of Learning Cycle 5E learning model on concept mastery and creative thinking ability of students on renewable energy material at SMAN 1 Gerung. The research method used is a pseudo-experimental method with a pre-test and post-test control group design. The research population used in this study were Phase E students of class X SMAN 1 Gerung. Samples were taken using purposive sampling technique and obtained XH class students as experimental class and XK as control class. The research instrument includes a description test that measures mastery of concepts and creative thinking skills that have been tested for validity, reliability, difficulty level of questions, and differentiation of questions. Data analysis used t-test and MANOVA. The results showed that the Learning Cycle 5E model significantly improved students' concept mastery and creative thinking skills compared to the conventional learning method. The average post-test score in the experimental group was higher than the control group, showing the effect of the Learning Cycle 5E model on students' concept mastery and creative thinking on renewable energy material with a significance showing 0.000. So this model provides opportunities for participants to be more active, critical, and creative in the learning process, and helps students better understand abstract and complex concepts. The implication of this research is the need for the application of innovative learning models such as Learning Cycle 5E to improve the quality of physics learning in schools, so that students can achieve the skills demanded by the curriculum and be able to compete in today's educational challenges.